Pfeiffer syndrome type 2: case report - Oyamada, Maria Kiyoko; Ferreira, Haideé Salgado Alonso; Hoff, Marcelo (São Paulo Medical Journal, 2003)
OBJECTIVE: To report on a case of Pfeiffer Syndrome, with a discussion of the diagnostic characteristics and features of disease types and the differential diagnosis. DESCRIPTION: The authors describe a newborn with cloverleaf skull, extreme bilateral exorbitism and choanal atresia, partial syndactyly of the second and third toes and broad medially-deviated big toes. The case reported was Pfeiffer Syndrome type 2, which usually has a poor prognosis. COMMENTS: Pfeiffer Syndrome is a clinically variable disorder and consists of an autosomal dominantly-inherited osteochondrodysplasia with craniosynostosis. It has been divided into three types. Type 1 is commonly associated with normal intelligence and generally good outcome. Types 2 and 3 generally have severe neurological compromise, poor prognosis, early death and sporadic occurrence. Potential for prolonged useful survival outcome can be achieved in some cases with early aggressive medical and surgical management according to recent literature.